A contextual analysis of cycling environment assessment tools in a Cape Town mobility corridor - Petzer, Brett (School of Architecture, Planning and Geomatics, 2017)
Building on recent research on barriers to cycling mobility in low-income South African contexts, this study explored the role of the built environment as a determinant of cycling practices along a mobility corridor in Cape Town, South Africa. The communities surveyed reflect the demographic and income disparities of the city, and their attitudes to cycling and the cycling environment both corroborate existing findings and pose new research questions. In particular, respondents of all income levels showed that they distorted their own journeys by bicycle to avoid areas perceived to have a high risk of criminal activity, even where this meant using routes perceived to present a high risk of physical injury. A second finding was that all road users engage in informal road behaviour, including motorists, and that this is an integral aspect of the study area's mobility culture. The methods used in this study were a series of interviews with three community bicycle-shop owners, supported by focus groups held in each community, and accompanied by a mapping exercise. Fieldwork took the form of accompaniment of youth cycling initiatives and observation of commuting practices by the author. The data obtained in fieldwork were then used to evaluate a selection of cycling environment assessment tools from the USA, UK and Australia, and a pedestrian environment assessment tool from South Africa, in order to evaluate their contextual appropriateness for the local determinants of cycling. The study concludes with recommendations towards a South African cycling environment assessment tool that would capacitate local government and civil society to deliver improvements to the cycling environment and capitalise on existing pro-cycling policies.